The Development of e-UKBM of Acid-Bases in Chemistry Based on Problem Based Learning Integrated with Sikkanese Lokal Culture: The Development of e-UKBM of Acid-Base in Chemistry Based on Problem-Based Learning Integrated with Sikkanese Local Culture (Jurnal TEKNODIK, 2022)
This research is motivated by the problem of using learning resources that are less effective on pandemic time and the boredom of students to attend the chemistry learning process especially acid-base material. To overcome it, the researchers tried to research the development of Independent Learning Activity Unit (e-UKBM) to facilitate learning activity work from home period. The learning method in e-UKBM is adopting problem based learning model which is integrated by Sikkanese local cultural. The method used is research and development by using 4D development models (Define, Design, Develop, and Disseminate). The subject of research are the 4 teachers and 60 students of class XI of SMAN 1 Maumere, SMAN 2 Maumere and SMAK St. Gabriel Maumere. Based on the result calculation of the percentage of validity obtained a value of 81.52% (valid). Furthermore, e-UKBM of Chemistry is suitable used in chemistry learning process in accordance with initial field trial result and wide field trial. Initial field trial by students is 102.37 (good category) and teacher is 105.00 (good category). Wide field test by students is 129. 05 (very good category) and teachers is 144.00 (very good category).
Keywords: acid-base; chemistry e-UKBM; Sikkanese local culture; problem based learning